Design and Development of A Vertical Wind Turbine Using Slow Wind Speed for Mini Power Generation - Din, Abdul Talib; Azraai, Shamsul Bahari; Thenamirtham, Kesavan Selvan (2012)
Wind energy can be changed into other forms of energy, either mechanical or electrical energy. To convert the kinetic energy into electricity, the wind turbines, which consists rotor blades, shaft and electricity generator is needed. Rotor blade is the most important part because when the wind forces the blades to move, it will transfer most of its energy to the rotor. Then the rotor transfers its mechanical, rotational energy to the shaft, whereby it is connected to the center of the rotor before enters an electrical generator on the other end. The aim of this study is to investigate the possibility of improving wind energy capture, under low wind speed conditions using various blade configurations. This paper deals with the results of the first part of the study which is the development of the methodology using physical test rig and computer modeling using commercial computational fluid dynamics (CFD) code. This study focuses mainly on analyzing the efficiency of the energy conversion and torque coefficients in relation to the tip speed ratio of wind turbine. For the overall performance, the results show that the output power produced by the wind turbine has great potential to be used in the slow wind region in the range of 5 to 10 km/hr.